2013
DOI: 10.1155/2013/149120
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake Mechanism of Cd(II), Cr(VI), Cu(II), Pb(II), and Zn(II) by Mycelia and Fruiting Bodies ofGalerina vittiformis

Abstract: Optimum concentrations of heavy metals like copper, cadmium, lead, chromium, and zinc in soil are essential in carrying out various cellular activities in minimum concentrations and hence help in sustaining all life forms, although higher concentration of these metals is lethal to most of the life forms. Galerina vittiformis, a macrofungus, was found to accumulate these heavy metals into its fleshy fruiting body in the order Pb(II) > Cd(II) > Cu(II) > Zn(II) > Cr(VI) from 50 mg/kg soil. It possesses various ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Further, the amount of adsorbed Pb 2+ per mass unit increased with the increase in initial lead ion concentration (Ezzouhri et al, 2010). The stable lead studies in some macromycetes have indicated that they produced two types of phytochelatins which played a crucial role in removing metals from soil (Damodaran et al, 2013). We might expect similar results in the case of radiolead 210 Pb.…”
Section: Statistical Analysis and Results Discussionmentioning
confidence: 64%
“…Further, the amount of adsorbed Pb 2+ per mass unit increased with the increase in initial lead ion concentration (Ezzouhri et al, 2010). The stable lead studies in some macromycetes have indicated that they produced two types of phytochelatins which played a crucial role in removing metals from soil (Damodaran et al, 2013). We might expect similar results in the case of radiolead 210 Pb.…”
Section: Statistical Analysis and Results Discussionmentioning
confidence: 64%
“…Earlier, intracellular thiol compounds have been reported for binding and accumulation of metal ions into intracellular space and vacuoles, respectively, thus resulting into increased tolerance level and lower cytoplasmic toxicity (Damodaran et al . 2013). Therefore, it could be concluded that tolerance or toxicity might depend upon the concentration of the simultaneous production of ROS and thiol compounds under heavy metal stress, which may further affect the mycelial surface morphology.…”
Section: Resultsmentioning
confidence: 99%
“…At neutral pH, metal binding to phytic acid corresponds to Cu > Zn > Ni > Co > Mn > Fe > Ca [ 43 ]. The cap of mushrooms produces stress-related factors (metallothionein) that govern the uptake of metal ions [ 44 ]. Cysteine-rich oligopeptides (phytochelatin family) bind a large fraction of cadmium in the caps of B. edulis when the edible mushroom is exposed to excess metals [ 45 ].…”
Section: Fungal Uptake Of Metals/metalloids With Neurotoxic Potentmentioning
confidence: 99%